Psychological maltreatment, psychological adjustment, family communication, and mental wellbeing: a longitudinal serial mediation study - ÜMMET, DURMUŞ (My University, 2023)
The fact that the relationships between psychological maltreatment, psychological adjustment, family communication and mental wellbeing have not been examined together in any longitudinal study has created a gap in the literature. In this study, a longitudinal design was used to examine whether psychological adjustment and family communication serially mediate the relationship between psychological maltreatment and mental wellbeing in a Turkish adults (age range = 19–63 years). Structural equation modelling (SEM) was used to test longitudinal serial mediation at two time waves SEM indicated that psychological adjustment and family communication have a longitudinal serial mediating role in the association between psychological maltreatment and mental wellbeing. Current research reveals that psychological adjustment and family communication are powerful tools for the wellbeing of those who have experienced psychological maltreatment.
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Eğitim Bilimleri; Psikolojik Danışma ve Rehberlik; Social Sciences and Humanities; Education; Educational Sciences; Guidance and Psychologicial Counseling; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities